Halogen-free antistatic agent and adhesive composition

CN122910291APending Publication Date: 2026-10-13THE JAPAN CARLIT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202580020466.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-22
Filing Date
2025-01-30
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

若限定为无卤素抗静电剂,已知有季铵阳离子为四烷基铵阳离子的抗静电剂,但对于这些无卤素抗静电剂而言,若四烷基铵阳离子中的烷基的碳数的合计过少,则赋予至粘合剂时耐湿热特性、粘合力降低,若过多则抗静电能力低,当对粘合剂赋予抗静电剂时,表面电阻值存在课题

Benefits of technology

[0030]关于本发明的抗静电剂,树脂相容性高,少量添加便可表现充分的抗静电能力。因此,只要将本发明的抗静电剂用于粘合剂组合物,便可形成在维持粘合力的同时耐湿热特性、透明性优异、雾度小的抗静电性粘合树脂,可用于保护光学构件表面、电子材料构件的表面保护膜。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122910291A_ABST
    Figure CN122910291A_ABST
Patent Text Reader

Abstract

The present application provides an antistatic agent containing an ammonium salt represented by formula (1) and an adhesive composition containing the same, and an antistatic agent and the like having excellent resin compatibility and antistatic properties using an antistatic resin. (In the formula, R1 to R4 can be the same or different and are alkyl groups having a carbon number of 1 to 13, and the total of the carbon numbers of the alkyl groups of R1 to R4 is 12 to 16.)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to antistatic agents using onium salts without halogen atoms formed from tetraalkylammonium cations and dioxaborate anions, as well as adhesive compositions containing the same and antistatic resins. Background Technology

[0002] As a method for imparting antistatic properties to insulating resins, a known method is to coat the surface of a resin matrix with a conductive coating containing an antistatic agent. Examples of such antistatic agents include electron-conducting materials such as carbon black and ITO; however, when used in adhesives that utilize resins, issues arise regarding the hardness and transparency of the adhesive layer. As an antistatic agent that maintains the transparency of the adhesive layer while imparting conductivity, ion-conducting materials using onium salts are known.

[0003] Ion-conductive materials are antistatic agents formed from ionic compounds of anions and cations, and various applications have been studied based on their properties. By varying the type and amount of ion-conductive material added to insulating resins, the resistivity of the resin used as a raw material is reduced, thereby enabling the manufactured resin material to exhibit different antistatic properties for various purposes.

[0004] In addition, onium salts possess excellent properties such as non-volatility, flame retardancy, and high ionic conductivity, and can be designed with various physical properties and functions, thus attracting considerable attention. Based on these properties, onium salts are used as antistatic agents for various resins.

[0005] As shown in Patent Documents 1 and 2, when using onium salts to impart antistatic properties to adhesives, ionic liquids containing fluorine anions, such as bis(trifluoromethanesulfonyl)imide and bis(fluorosulfonyl)imide, are known to be used. However, these antistatic agents use halogens such as fluorine. From the perspective of corrosion of metals and the recent PFAS regulations, halogen-free antistatic agents are desired. As shown in Patent Document 3, in the semiconductor field, antistatic agents whose anions do not contain fluorine are used in tape applications.

[0006] It is known that halogen-free onium salts are inferior to conventional onium salts containing fluorine anions in terms of physical properties. For example, as shown in Patent Document 4, halogen-free antistatic agents using tetraalkylammonium cations and dodecylbenzenesulfonic acid anions have lower antistatic capabilities, and surface resistivity becomes an issue when antistatic agents are applied to adhesives.

[0007] Patent Document 5 discloses antistatic agents that utilize quaternary ammonium cations and bis(oxalato)borate anions. Patent Document 5 presupposes that the quaternary ammonium cation can also have a halogenated hydrocarbon group structure, without considering halogen-free formulations. While antistatic agents with tetraalkylammonium cations are known, for these halogen-free antistatic agents, if the total number of carbon atoms in the alkyl groups of the tetraalkylammonium cation is too low, the moisture resistance and adhesion of the adhesive decrease; if it is too high, the antistatic ability is low. When antistatic agents are applied to adhesives, surface resistivity becomes an issue.

[0008] Existing technical documents

[0009] Patent documents

[0010] Patent Document 1: Japanese Patent Application Publication No. 2005-290357

[0011] Patent Document 2: Japanese Patent Application Publication No. 2013-064146

[0012] Patent Document 3: Japanese Patent Application Publication No. 2022-109631

[0013] Patent Document 4: Japanese Patent Application Publication No. 2023-034983

[0014] Patent Document 5: Japanese Patent Application Publication No. 2019-108414 Summary of the Invention

[0015] The problem that the invention aims to solve

[0016] The object of this invention is to provide an antistatic agent that is halogen-free in its molecular structure, has excellent resin compatibility, and exhibits sufficient antistatic ability when added in small amounts. Furthermore, the object is to provide adhesive compositions with excellent transparency and low haze, as well as antistatic adhesive resins with excellent resistance to damp heat, by using such an antistatic agent in adhesives.

[0017] Methods for solving problems

[0018] Through in-depth research, the inventors discovered that by using a tetraalkylammonium cation obtained by setting the total number of carbon atoms of the alkyl groups in the tetraalkylammonium cation to 12 to 16, an antistatic agent with excellent resin compatibility and antistatic ability, an adhesive composition with excellent transparency and low haze, and an antistatic adhesive resin with excellent resistance to damp heat while maintaining adhesive strength, thus completing the present invention.

[0019] The present invention is as shown in [1] to [6] below.

[0020] [1] An antistatic agent comprising the quaternary ammonium salt represented by formula (1),

[0021] [Chemical Formula 1]

[0022]

[0023] (In the formula, R1 to R4 are alkyl groups with 1 to 13 carbon atoms that may be the same or different, and the total number of carbon atoms of the alkyl groups R1 to R4 is 12 to 16).

[0024] [2] The antistatic agent as described in [1], wherein the quaternary ammonium salt shown in the above formula (1) is tetrabutylammonium = dioxaborate or tetrapropylammonium = dioxaborate.

[0025] [3] An antistatic resin, characterized in that it contains an antistatic agent as described in any one of [1] to [2] and a resin.

[0026] [4] An adhesive composition, characterized in that it contains an antistatic agent as described in any one of [1] to [2] and an acrylic adhesive.

[0027] [5] The adhesive composition described in [4] is characterized in that it contains 0.1 to 10 parts by weight of an antistatic agent relative to 100 parts by weight of the resin component of the acrylic adhesive.

[0028] [6] An antistatic adhesive resin, characterized in that it is formed by coating with an adhesive composition described in any one of [4] to [5], and its surface resistivity is less than 1.0 × 10⁻⁶. 10 Ω.

[0029] Invention Effects

[0030] The antistatic agent of the present invention exhibits high resin compatibility, and sufficient antistatic ability can be achieved with a small amount of addition. Therefore, by using the antistatic agent of the present invention in an adhesive composition, an antistatic adhesive resin with excellent resistance to damp heat, excellent transparency, and low haze can be formed while maintaining adhesive strength. It can be used to protect the surface of optical components and the surface protective film of electronic material components. Detailed Implementation

[0031] The present invention will now be described. It should be noted that the present invention is not limited to the following embodiments.

[0032] [Quaternary ammonium salt]

[0033] The antistatic agent of the present invention comprises a quaternary ammonium salt as shown in formula (1). The quaternary ammonium salt comprises a tetraalkylammonium cation and a bis(oxalato)borate anion.

[0034] [Chemical Formula 2]

[0035]

[0036] In formula (1), R1 to R4 are alkyl groups with 1 to 13 carbon atoms, which may be the same or different, and the total number of carbon atoms in the alkyl groups R1 to R4 is 12 to 16. In addition, the alkyl group may be either straight-chain or branched. Specific alkyl groups include methyl, ethyl, propyl, isopropyl, cyclopropyl, butyl, sec-butyl, tert-butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, and tridecyl.

[0037] Specific examples of the tetraalkylammonium cations represented by formula (1) above include: tetrapropylammonium cation, tetrabutylammonium cation, trimethylnonammonium cation, trimethyldecaneammonium cation, trimethylundecaneammonium cation, trimethyldodecaneammonium cation, trimethyltridecaneammonium cation, triethylhexammonium cation, triethylheptammonium cation, triethyloctammonium cation, triethylnonammonium cation, triethyldecaneammonium cation, tripropylbutylammonium cation, tripropylpentaneammonium cation, tripropylhexammonium cation, tripropylheptammonium cation, tributylmethylammonium cation, tributylethylammonium cation, tributylpropylammonium cation, tributylmethylammonium cation, dimethyldipentaneammonium cation, dimethyldihexammonium cation, dimethyldiheptammonium cation, and dipropyldibutylammonium cation. Dipropyl dipentanemonium cation, dimethyl ethyl octanemonium cation, dimethyl ethyl nonanium cation, dimethyl ethyl decanemonium cation, dimethyl ethyl undecanemonium cation, dimethyl ethyl dodecanemonium cation, dimethyl propyl heptanemonium cation, dimethyl propyl octanemonium cation, dimethyl propyl nonanium cation, dimethyl propyl decanemonium cation, dimethyl propyl undecanemonium cation, dimethyl butyl hexamium cation, dimethyl butyl heptanemonium cation, dimethyl butyl octanemonium cation, dimethyl butyl nonanium cation, dimethyl butyl decanemonium cation, dimethyl pentyl hexamium cation, dimethyl pentyl heptanemonium cation, dimethyl pentyl octanemonium cation, dimethyl pentyl nonanium cation, dimethyl hexyl heptanemonium cation, dimethyl hexyl octanemonium cation, diethyl Methylheptane ammonium cation, diethylmethyloctane ammonium cation, diethylmethylnonane ammonium cation, diethylmethyldecane ammonium cation, diethylmethylundecane ammonium cation, diethylpropylpentane ammonium cation, diethylpropylhexane ammonium cation, diethylpropylheptane ammonium cation, diethylpropyloctane ammonium cation, diethylpropylnonane ammonium cation, diethylmethylpentane ammonium cation, diethylmethylhexane ammonium cation, diethylmethylheptane ammonium cation, diethylmethyloctane ammonium cation, diethylmethylnonane ammonium cation, diethylethylbutylammonium cation, diethylethylpentane ammonium cation, diethylethylhexane ammonium cation, diethylethylheptane ammonium cation, diethylethyloctane ammonium cation, diethylbutylpentane ammonium cation, diethylbutylhexane ammonium cation, dibutylmethylpropylpentane ammonium cation Ammonium cation, dibutylmethylpentanium cation, dibutylmethylhexammonium cation, dibutylmethylheptanium cation, dibutylethylpropylammonium cation, dibutylethylpentanium cation, dibutylethylhexammonium cation, dibutylpropylpentanium cation, methylethylpropylhexammonium cation, methylethylpropylheptanium cation, methylethylpropyloctanium cation, methylethylpropylnonanium cation, methylethylpropyldecaneanium cation, methylethylbutylpentanium cation, methylethylbutylhexammonium cation, methylethylbutylheptanium cation, methylethylbutyloctanium cation, methylethylbutylnonanium cation, methylethylpentylhexammonium cation, methylethylpentylheptanium cation, methylethylpentyloctanium cation, methylethylhexylheptanium cationThe cations include methylpropyl butylpentanemonium cation, methylpropyl butylhexanemonium cation, methylpropyl butyl heptanemonium cation, methylpropyl butyl octanemonium cation, methylpropyl pentanehexanemonium cation, methylpropyl pentanehexanemonium cation, methylbutyl pentanehexanemonium cation, ethylpropyl butylpentanemonium cation, ethylpropyl butylhexanemonium cation, ethylpropyl butyl heptanemonium cation, ethylpropyl pentanehexanemonium cation, etc. Among these tetraalkylammonium cations, tetrapropylammonium cation, tetrabutylammonium cation, trimethylnonanemonium cation, trimethyldecanemonium cation, trimethyldodecanemonium cation, tributylmethylammonium cation, and dimethylhexyloctanemonium cation are preferred. From the perspective of balancing antistatic properties and resin compatibility, as well as resistance to damp heat, tetrapropylammonium cation (the total number of carbon atoms in the alkyl groups is 12) and tetrabutylammonium cation (the total number of carbon atoms in the alkyl groups is 16) are more preferred.

[0038] In formula (1), the anion represents bis(oxalate-borate) ions.

[0039] Regarding the antistatic agent of the present invention, among the onium salts shown in formula (1), tetrabutylammonium = dioxolane or tetrapropylammonium = dioxolane is preferred.

[0040] The onium salt shown in formula (1) above can be manufactured using known methods to achieve the above structure. Examples of such methods include the following. It should be noted that the compound used in this reaction can be a commercially available compound synthesized by known methods.

[0041] [Method for manufacturing ium salts]

[0042] [Chemical Formula 3]

[0043]

[0044] Specific examples of the tetraalkylammonium cation shown in formula (2) above include tetrapropylammonium cation, tetrabutylammonium cation, trimethylnonammonium cation, trimethyldecaneammonium cation, trimethyldodecaneammonium cation, tributylmethylammonium cation, and dimethylhexyloctaneammonium cation. Examples of halides that form the counter anions of the above cations include chloride ions, bromide ions, and iodide ions.

[0045] Examples of metal salts that can be used as formula (3) include lithium bis(oxalato)borate, sodium bis(oxalato)borate, and potassium bis(oxalato)borate.

[0046] Examples of alkali metals and transition metals that can counteract the aforementioned anions include lithium, sodium, potassium, and silver.

[0047] The amount of formula (3) used in the ion exchange reaction is usually 0.8 moles or more relative to 1 mole of formula (2), preferably 0.9 to 1.8 moles, and more preferably 1.0 to 1.2 moles.

[0048] Ion exchange reactions are usually carried out in a solvent. There are no particular restrictions on the solvent, as long as it does not affect the reaction. Specifically, examples include pure water, acetonitrile, ethyl acetate, benzene, toluene, xylene, diethyl ether, tetrahydrofuran, and 1,4-dioxane, with pure water and acetonitrile being preferred.

[0049] There is no particular restriction on the mixing order of formulas (2), (3) and solvent. Formula (3) can be added after mixing formula (2) with solvent, or formula (2) can be added after mixing formula (3) with solvent.

[0050] The reaction temperature during ion exchange is usually above 10°C, preferably 10–60°C, and particularly preferably 15–50°C.

[0051] When separating formula (4) from the reaction solution after the reaction is complete, the solvent and the generated inorganic salts are removed from the reaction solution. If inorganic salts precipitate in the obtained reaction solution, the reaction solution is filtered to remove the precipitated inorganic salts. Then, formula (4) is separated by appropriately combining unit operations such as concentration, filtration, and extraction. Formula (4) obtained by separation can be used as an antistatic agent.

[0052] The antistatic agent of the present invention thus obtained is halogen-free because its molecular structure does not contain halogens. Furthermore, the antistatic agent of the present invention, which is formed by combining a tetraalkylammonium cationic skeleton obtained by setting the total number of carbon atoms of the alkyl groups in the bis(oxalato)borate anion and the tetraalkylammonium cation to be 12 to 16, exhibits lower ionic conductivity compared to the case where the total number of carbon atoms of the alkyl groups in the tetraalkylammonium cation is greater than 12 to 16, and compared to the case where the total number of carbon atoms of the alkyl groups in the tetraalkylammonium cation is smaller than 12 to 16, it achieves better antistatic properties with superior resin compatibility and hydrophobicity.

[0053] [Adhesive Compositions and Antistatic Adhesive Resins]

[0054] By combining the antistatic agent of the present invention with an acrylic adhesive, an adhesive composition endowed with antistatic properties can be obtained. This antistatic adhesive composition, by containing it, becomes an antistatic adhesive resin. This antistatic adhesive resin is a resin with excellent antistatic properties, excellent transparency, and low haze. This antistatic adhesive resin also improves its resistance to damp heat while maintaining adhesive strength. Specifically, the surface resistivity of the antistatic adhesive resin formed from the adhesive composition is 5.0 × 10⁻⁶. 10Ω or less, more preferably 1.0 × 10 10 The surface resistivity is below Ω, the transmittance is above 90% in terms of transparency, and the haze value is below 2.0%, preferably below 1.5%. Furthermore, the change rate of adhesive force before and after adding the antistatic agent is less than 10%, and the change rate of haze before and after the damp heat resistance test of the antistatic adhesive resin is less than 10%. It should be noted that the surface resistivity value is a value measured using a resistivity meter, the transmittance and haze value are values ​​measured using a haze meter, the adhesive force is a value measured using a tensile testing machine, and in the damp heat resistance test, the haze value can be measured using a haze meter after being placed under certain temperature and humidity conditions. Therefore, the adhesive composition of the present invention contains at least the above-mentioned quaternary ammonium salt and acrylic adhesive. It should be noted that the adhesive ink prepared by dissolving the above-mentioned adhesive composition in a soluble organic solvent is included in the adhesive composition of the present invention. Furthermore, the antistatic adhesive resin of the present invention also includes adhesive sheets, adhesive films, and materials obtained by peeling the above-mentioned adhesive ink from a substrate. Additionally, the antistatic adhesive resin of the present invention is used as a material commonly referred to as an adhesive layer.

[0055] The acrylic adhesive of the present invention preferably contains an acrylic polymer, which is mainly composed of acrylates or methacrylates having alkyl groups having 1 to 14 carbon atoms. Specifically, examples include methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, tert-butyl methacrylate, isobutyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, and n-octyl acrylate.

[0056] Acrylic polymers can be obtained through common acrylic polymer polymerization methods such as solution polymerization, emulsion polymerization, bulk polymerization, and suspension polymerization, and can also be any of random copolymers, block copolymers, graft copolymers, etc.

[0057] Furthermore, by appropriately crosslinking acrylic polymers, adhesive compositions with adhesive layers exhibiting excellent heat resistance can be obtained. Crosslinking methods include adding a crosslinking agent to the acrylic adhesive. Examples of crosslinking agents include isocyanate compounds, epoxy compounds, aziridine compounds, and metal chelate compounds.

[0058] Isocyanate compounds are compounds that have at least two isocyanate groups (-NCO) within their molecules. Specifically, examples include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic diisocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and phenylenediamine diisocyanate; trimer adducts of trimethylolpropane / toluene diisocyanate; trimer adducts of trimethylolpropane / hexamethylene diisocyanate; and isocyanurate derivatives of hexamethylene diisocyanate.

[0059] Epoxy compounds are compounds that have at least two epoxy groups in their molecules. Examples include bisphenol A type epoxy resins, ethylene glycol diglycidyl ether, glycerol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and N,N-diglycidyl aniline.

[0060] Aziridine compounds are compounds that have at least two three-membered ring skeletons, also known as ethyleneimines, formed by one nitrogen atom and two carbon atoms within the molecule. Examples include diphenylmethane-4,4'-bis(1-aziridinecarboxamide), toluene-2,4-bis(1-aziridinecarboxamide), triethylene melamine, isophthaloylbis-1-(2-methylaziridine), tri-1-aziridineylphosphine oxide, hexamethylene-1,6-bis(1-aziridinecarboxamide), trimethylolpropane-tris((β-aziridine)propionate), and tetramethylolmethane-tris((β-aziridine)propionate), among others.

[0061] Examples of metal chelate compounds include those containing acetylacetone or ethyl acetoacetate coordinated to polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium.

[0062] The content of the crosslinking agent is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 5.0 parts by weight, relative to 100 parts by weight of the acrylic adhesive. When it is less than 0.01 parts by weight, the cohesive strength of the adhesive composition decreases due to insufficient crosslinking, and sometimes sufficient heat resistance cannot be obtained. On the other hand, when it exceeds 10 parts by weight, the cohesive strength of the polymer increases and the fluidity decreases, resulting in insufficient wetting of the adhered material, which sometimes becomes a cause of peeling.

[0063] The adhesive composition of the present invention may also contain a surfactant comprising an oxyalkylene compound. An oxyalkylene compound is a compound having an oxyalkylene group; specifically, examples include oxyalkylene surfactants, oxyalkylene polyether polymers, and (meth)acrylic polymers containing alkylene glycol groups. Among these, oxyalkylene surfactants are preferred because they have good compatibility with acrylic polymers.

[0064] Examples of oxyalkylene-containing surfactants include: nonionic surfactants such as polyoxyalkylene fatty acid esters, polyoxyalkylene dehydrated sorbitan fatty acid esters, polyoxyalkylene sorbitan fatty acid esters, polyoxyalkylene alkyl ethers, polyoxyalkylene alkyl allyl ethers, polyoxyalkylene alkylbenzene ethers, polyoxyalkylene derivatives, polyoxyalkylene alkylamines, and polyoxyalkylene alkylamine fatty acid esters; anionic surfactants such as polyoxyalkylene alkyl ether sulfates, polyoxyalkylene alkyl ether phosphates, polyoxyalkylene alkylbenzene ether sulfates, and polyoxyalkylene alkylbenzene ether phosphates; and cationic and biionic surfactants containing oxyalkylene groups. Additionally, reactive substituents such as (meth)acryloyl and allyl groups may also be present in the molecule.

[0065] Oxyalkylene compounds can be used alone or in combination of two or more. The preferred amount is 0.01 to 10 parts by weight, more preferably 0.05 to 5 parts by weight, relative to 100 parts by weight of the acrylic polymer. When the amount is less than 0.01 parts by weight, exudation may sometimes occur.

[0066] Furthermore, the adhesive composition of the present invention may also contain silane compounds. By containing silane compounds, adhesion to substrates such as films and glass can be improved.

[0067] Examples of silane compounds include: vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-epoxypropoxypropyltrimethoxysilane, 3-epoxypropoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-epoxypropoxypropyltrimethoxysilane, 3-epoxypropoxypropyltriethoxysilane, 3-epoxypropoxypropyldimethoxymethylsilane, and 3-epoxypropoxypropylethoxydimethylsilane. These can also be used in combination with more than one type.

[0068] The amount of the quaternary ammonium salt represented by formula (1) in the adhesive composition of the present invention is preferably 0.01 to 20 parts by weight, more preferably 0.1 to 10 parts by weight, relative to 100 parts by weight of the acrylic adhesive. By setting the amount in this range, an adhesive composition with superior electrical properties can be obtained.

[0069] The adhesive composition of the present invention may be used in combination with other adhesive resins, antioxidants, ultraviolet absorbers, slip agents, etc., without impairing the effects of the present invention.

[0070] When an adhesive sheet with an adhesive layer formed on a substrate is manufactured as an antistatic adhesive resin, the adhesive composition of the present invention can be directly applied to the substrate, or the adhesive composition can be dissolved in a soluble organic solvent and the resulting adhesive ink can be applied to the substrate. After applying these adhesive compositions or adhesive inks to substrates such as resin films or glass, they are dried as needed, thereby producing an adhesive sheet with an adhesive layer formed on the surface of these substrates. The thickness of the adhesive layer is preferably 3 to 100 μm, more preferably 5 to 50 μm.

[0071] [Adhesive Inks]

[0072] Regarding the organic solvents used in adhesive inks as adhesive compositions, examples include: alcohol-based solvents such as methanol, ethanol, propanol, isopropanol (IPA), and butanol; glycol-based solvents such as ethylene glycol, propylene glycol, butanol, polyethylene glycol, polypropylene glycol, and polyoxyethylene-polyoxypropylene copolymer; and monomethyl ether, monoethyl ether, monopropyl ether, monoisopropyl ether, and monoethyl ether of the above glycol-based solvents. Ether-based solvents such as butyl ether; polyether solvents such as dimethyl ether, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, methyl ethyl ether, methyl propyl ether, methyl isopropyl ether, methyl butyl ether, ethyl propyl ether, ethyl isopropyl ether, and ethyl butyl ether; ketone solvents such as methyl ethyl ketone (MEK), methyl isobutyl ketone, and cyclohexanone; ester solvents such as methyl acetate, ethyl acetate, and butyl acetate; and hydrocarbon solvents such as hexane, heptane, octane, cyclopentane, cyclohexane, toluene, and xylene. Among these, toluene, MEK, ethyl acetate, butyl acetate, and IPA are particularly preferred.

[0073] [Substrate]

[0074] Examples of substrates include polyethylene terephthalate (PET) film, polycarbonate film, polystyrene film, acrylic film, cellulose triacetate film, polyethylene film, and polypropylene film.

[0075] [How to make adhesive sheets]

[0076] Examples of methods for coating a substrate with an adhesive composition include roller coating, gravure coating, reverse coating, die coating, and comma coating. When drying is performed to remove the solvent from the liquid film coated on the substrate, etc., from the viewpoint of promoting the curing of the liquid film, the temperature is preferably 50°C or higher and 150°C or lower.

[0077] To protect the adhesive surface, spacers can be attached to the surface of the adhesive layer as needed. The spacers can be paper or plastic film; plastic film is more suitable due to its superior surface smoothness.

[0078] Examples of plastic films include polyethylene film, polypropylene film, polybutene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, polyethylene terephthalate film, polybutylene terephthalate film, and polyurethane film.

[0079] The adhesive composition of the present invention, or the adhesive sheet (antistatic adhesive resin) made therefrom, can be used in plastic products, etc. In particular, it can be used as: a surface protective film for protecting the surface of optical components such as polarizing plates, wavelength plates, optical compensation films, light diffusers, and reflectors used in liquid crystal displays, etc.; and a protective film for electronic materials and semiconductor components.

[0080] [Antistatic resin]

[0081] As described above, the antistatic agent of the present invention, when combined with acrylic adhesives, can yield an adhesive composition endowed with antistatic properties. Of course, by containing it alone in various resins, it can also impart conductivity to the resin, thus creating an antistatic resin. Examples of resins that may contain the antistatic agent of the present invention, besides acrylic adhesives, include synthetic resins such as polyethylene terephthalate, polypropylene, and polycarbonate, as well as various adhesives or release agents (silicone adhesives, urethane adhesives, rubber adhesives, silicone release agents, fluorinated release agents, acrylic release agents, etc.). It should be noted that the properties of the antistatic resin of the present invention are the same as those of the aforementioned adhesive layer (antistatic adhesive resin).

[0082] The antistatic resin of the present invention can be manufactured in the same manner as antistatic resins using conventionally known antistatic agents. In addition to acrylic adhesives, the resin can be, for example, synthetic resins such as polyethylene terephthalate, polypropylene, and polycarbonate, as well as various adhesives or release agents (silicone adhesives, urethane adhesives, rubber adhesives, silicone release agents, fluorinated release agents, acrylic release agents, etc.), and can be mixed with them to obtain the antistatic resin. Furthermore, if an acrylic resin monomer is used as a raw material for the resin, a solution is prepared by adding a photopolymerization initiator to a solution containing the acrylic resin monomer and the antistatic agent of the present invention, and the resin coated with this solution is irradiated with ultraviolet light to obtain the antistatic resin of the present invention.

[0083] [Example]

[0084] The present invention will be described in detail below with reference to embodiments, but the present invention is not limited to these embodiments.

[0085] [Manufacturing of antistatic agents]

[0086] Tetrabutylammonium = dioxaborate ion is produced as follows.

[0087] 16 g of tetrabutylammonium bromide and 15 g of acetonitrile were added to a four-necked flask. 10 g of lithium bis(oxalato)borate was then added to the mixture, and the mixture was stirred at 40°C for 1 hour. After removing the solvent by concentration, the mixture was washed with butyl acetate and pure water, and then concentrated again to obtain 20 g of tetrabutylammonium (the total number of carbon atoms in the alkyl groups is 16) bis(oxalato)borate (yield 94%).

[0088] (Example 1)

[0089] [Making of Adhesive Inks]

[0090] • Acrylic adhesive (manufactured by Soken Chemical Co., Ltd., 2030U, 15% non-volatile components): 40g

[0091] • Curing agent (isocyanate compound, manufactured by Soken Chemical Co., Ltd., Y-75, 75% non-volatile components): 0.32g

[0092] • Antistatic agent (tetrabutylammonium = dioxazone-borate): 0.03g

[0093] The above components were diluted with MEK to a concentration of 15 parts by weight of non-volatile components to prepare an adhesive ink.

[0094] (Example 2)

[0095] The adhesive ink was prepared without any changes except that 0.06g of the antistatic agent in Example 1 was used to replace 0.03g of the antistatic agent.

[0096] (Example 3)

[0097] The adhesive ink was prepared without any changes except that 0.12g of the antistatic agent in Example 1 was used to replace 0.03g of the antistatic agent.

[0098] (Example 4)

[0099] The adhesive ink was prepared without any changes except that 0.60g of the antistatic agent in Example 1 was used to replace 0.03g of the antistatic agent.

[0100] [Manufacturing of antistatic agents]

[0101] Tetrapropylammonium = dioxaborate ion is produced as follows.

[0102] 13 g of tetrapropylammonium bromide and 15 g of acetonitrile were added to a four-necked flask. 10 g of lithium bis(oxalato)borate was then added to the mixture, and the mixture was stirred at 40°C for 1 hour. After removing the solvent by concentration, the mixture was washed with butyl acetate and pure water, and then concentrated again to obtain 17 g of tetrapropylammonium (the total number of carbon atoms in the alkyl groups is 12) bis(oxalato)borate (yield 93%).

[0103] (Example 5)

[0104] The adhesive ink was prepared without any changes except for the use of tetrapropylammonium dioxolane-borate to replace the antistatic agent in Example 1.

[0105] (Example 6)

[0106] The adhesive ink was prepared without any changes except that 0.06g of the antistatic agent in Example 5 was used to replace 0.03g of the antistatic agent.

[0107] (Example 7)

[0108] The adhesive ink was prepared without any changes except that 0.12g of the antistatic agent in Example 5 was used to replace 0.03g of the antistatic agent.

[0109] (Example 8)

[0110] The adhesive ink was prepared without any changes except that 0.60g of the antistatic agent in Example 5 was used to replace 0.03g of the antistatic agent.

[0111] [Manufacturing of antistatic agents]

[0112] Tetraethylammonium = dioxaborate ion is produced as follows.

[0113] 10 g of tetraethylammonium bromide and 15 g of acetonitrile were added to a four-necked flask. 10 g of lithium bis(oxalato)borate was then added to the mixture, and the mixture was stirred at 40°C for 1 hour. After removing the solvent by concentration, the mixture was washed with butyl acetate and pure water, and then concentrated again to obtain 13 g of tetraethylammonium (the total number of carbon atoms in the alkyl groups is 8) bis(oxalato)borate (yield 86%).

[0114] (Comparative Example 1)

[0115] The adhesive ink was prepared without any changes except for the use of tetraethylammonium di(bis(oxalate)borate) to replace the antistatic agent in Example 1.

[0116] (Comparative Example 2)

[0117] Except for replacing 0.03g of the antistatic agent in Comparative Example 1 with 0.06g, the adhesive ink was prepared without any other changes.

[0118] (Comparative Example 3)

[0119] The adhesive ink was prepared without any changes except that 0.12g of the antistatic agent in Comparative Example 1 was replaced with 0.03g of the antistatic agent.

[0120] (Comparative Example 4)

[0121] Except for replacing 0.03g of the antistatic agent in Comparative Example 1 with 0.60g, the adhesive ink was prepared without any other changes.

[0122] [Manufacturing of antistatic agents]

[0123] The following is an example of manufacturing trimethylhexadecaneammonium = dioxaborate.

[0124] 18 g of trimethylhexadecaneammonium bromide and 15 g of acetonitrile were added to a four-necked flask. 10 g of lithium bis(oxalato)borate was then added to the mixture, and the mixture was stirred at 40°C for 1 hour. After removing the solvent by concentration, the mixture was washed with butyl acetate and pure water, and then concentrated again to obtain 22 g of trimethylhexadecaneammonium bromide (the total number of carbon atoms in the alkyl groups is 19) bis(oxalato)borate (yield 94%).

[0125] (Comparative Example 5)

[0126] The adhesive ink was prepared without any changes except for the use of trimethylhexadecanoic acid dioxazoborate to replace the antistatic agent in Example 1.

[0127] (Comparative Example 6)

[0128] The adhesive ink was prepared without any changes except that 0.06g of the antistatic agent in Comparative Example 5 was replaced with 0.03g of the antistatic agent.

[0129] (Comparative Example 7)

[0130] The adhesive ink was prepared without any changes except that 0.12g of the antistatic agent in Comparative Example 5 was replaced with 0.03g of the antistatic agent.

[0131] (Comparative Example 8)

[0132] The adhesive ink was prepared without any changes except that 0.60g of the antistatic agent in Comparative Example 5 was used to replace 0.03g of the antistatic agent.

[0133] [Manufacturing of antistatic agents]

[0134] Trioctylmethylammonium = dioxarate borate is produced as follows.

[0135] 20 g of trioctylmethylammonium bromide and 15 g of acetonitrile were added to a four-necked flask. 10 g of lithium bis(oxalato)borate was then added to the mixture, and the mixture was stirred at 40°C for 1 hour. After removing the solvent by concentration, the mixture was washed with butyl acetate and pure water, and then concentrated again to obtain 22 g of trioctylmethylammonium (the total number of carbon atoms in the alkyl groups is 25) bis(oxalato)borate (yield 87%).

[0136] (Comparative Example 9)

[0137] The adhesive ink was prepared without any changes except for the use of trioctylmethylammonium dioxolane-borate to replace the antistatic agent in Example 1.

[0138] (Comparative Example 10)

[0139] Except for replacing 0.03g of the antistatic agent in Comparative Example 9 with 0.06g, the adhesive ink was prepared without any other changes.

[0140] (Comparative Example 11)

[0141] Except for replacing 0.03g of the antistatic agent in Comparative Example 9 with 0.12g, the adhesive ink was prepared without any other changes.

[0142] (Comparative Example 12)

[0143] The adhesive ink was prepared without any changes except that 0.60g of the antistatic agent in Comparative Example 9 was used to replace 0.03g of the antistatic agent.

[0144] [Manufacturing of antistatic agents]

[0145] Tetrabutylammonium = dodecylbenzenesulfonic acid is manufactured as follows.

[0146] 16 g of tetrabutylammonium bromide, 18 g of sodium dodecylbenzenesulfonate, and 15 g of pure water were added to a four-necked flask and stirred at 60 °C for 15 hours. After removing the solvent by concentration, the mixture was washed with ethyl acetate and pure water, and then concentrated again to obtain 23 g of tetrabutylammonium-dodecylbenzenesulfonic acid (yield 82%).

[0147] (Comparative Example 13)

[0148] The adhesive ink was prepared without any changes except for the use of tetrabutylammonium-dodecylbenzenesulfonic acid to replace the antistatic agent in Example 1.

[0149] (Comparative Example 14)

[0150] The adhesive ink was prepared without any changes except that 0.06g of the antistatic agent in Comparative Example 13 was replaced with 0.03g of the antistatic agent.

[0151] (Comparative Example 15)

[0152] The adhesive ink was prepared without any changes except that 0.12g of the antistatic agent was used to replace 0.03g of the antistatic agent in Comparative Example 13.

[0153] (Comparative Example 16)

[0154] The adhesive ink was prepared without any changes except that 0.60g of the antistatic agent in Comparative Example 13 was used to replace 0.03g of the antistatic agent.

[0155] [Manufacturing of antistatic agents]

[0156] Tetrapropylammonium = dodecylbenzenesulfonic acid is manufactured as follows.

[0157] 13g of tetrapropylammonium bromide, 18g of sodium dodecylbenzenesulfonate, and 15g of pure water were added to a four-necked flask and stirred at 60°C for 15 hours. After removing the solvent by concentration, the mixture was washed with ethyl acetate and pure water, and then concentrated again to obtain 20g of tetrapropylammonium-dodecylbenzenesulfonic acid (yield 80%).

[0158] (Comparative Example 17)

[0159] The adhesive ink was prepared without any changes except for the use of tetrapropylammonium-dodecylbenzenesulfonic acid to replace the antistatic agent in Example 1.

[0160] (Comparative Example 18)

[0161] The adhesive ink was prepared without any changes except that 0.06g of the antistatic agent in Comparative Example 17 was used to replace 0.03g of the antistatic agent.

[0162] (Comparative Example 19)

[0163] The adhesive ink was prepared without any changes except that 0.12g of the antistatic agent in Comparative Example 17 was used to replace 0.03g of the antistatic agent.

[0164] (Comparative Example 20)

[0165] The adhesive ink was prepared without any changes except that 0.60g of the antistatic agent in Comparative Example 17 was used to replace 0.03g of the antistatic agent.

[0166] [Application Conditions]

[0167] The adhesive ink was applied to the PET film using a bar coater to a thickness of approximately 25 μm after drying. The film was then dried at 120°C for 3 minutes using a hot air dryer to produce a test piece (adhesive film).

[0168] [Surface resistivity measurement]

[0169] Using a Hiresta UP (manufactured by Mitsubishi Chemical Analytech Co., Ltd., product name "MCP-HT450"), the probe was pressed against the coated surface of the test piece at a temperature of 23±2℃, humidity of 50±5%RH, and applied voltage of 100V, and the stable surface resistance value was measured after 30 seconds.

[0170] [Determination of transmittance and haze value]

[0171] For the adhesive film after the spacer has been removed, the transmittance and haze on the adhesive layer side were measured using a haze meter (manufactured by Nippon Denshoku Kogyo Co., Ltd., product name "NDH5000").

[0172] [Determination of Adhesive Strength]

[0173] For the test specimens (25mm wide adhesive film pressed onto SUS304 steel plate using a 2kg roller), a tensile testing machine (Shimadzu Corporation, product name "AUTOGRAPH AGS-X 100 N") was used to peel the film at a 180° angle at a peel speed (300mm / min). The measured peel strength was defined as the adhesive force. It should be noted that the adhesive force was evaluated based on the rate of change in adhesive force before and after adding the antistatic agent, according to the following evaluation criteria. Furthermore, the test was only conducted on specimens with an antistatic agent concentration of 10% relative to the resin solids content.

[0174] Evaluation Criteria

[0175] 〇: The change rate of adhesive strength of the adhesive film before and after adding the antistatic agent is less than 10%.

[0176] ×: The change rate of adhesive strength of the adhesive film before and after adding the antistatic agent is more than 10%.

[0177] [Damp heat resistance test]

[0178] The haze of the test sample (a 25 mm wide adhesive film stored at 60°C and 80% RH for 500 hours) was measured using a haze meter (manufactured by Nippon Denshoku Kogyo Co., Ltd., product name "NDH5000") and evaluated according to the following evaluation criteria.

[0179] Evaluation Criteria

[0180] 〇: The change rate of haze value before and after the damp heat resistance test is less than 10%.

[0181] ×: The change rate of haze value before and after the damp heat resistance test is more than 10%.

[0182] The results of Examples 1-8 and Comparative Examples 1-20 are shown in Table 1.

[0183] [Table 1]

[0184]

[0185] As described above, the adhesive compositions of Examples 1 to 8 of the present invention, even when added in small amounts of 10% or less relative to the resin solids, still possess a sufficient surface resistivity (less than 1 × 10⁻⁶) when used as an adhesive film (antistatic adhesive resin) to impart antistatic properties. 10 The surface resistivity (Ω) also meets the criteria for resin compatibility, with a haze value of 1.5% or less and a transmittance of 90% or more. Furthermore, no problems were found with the resistance to damp heat. Regarding adhesion, even with the addition of 10% antistatic agent, almost no change was observed compared to before addition. On the other hand, while Comparative Examples 1-4 met the criteria for surface resistivity, their resistance to damp heat and adhesion changed significantly, and exudation occurred. For Comparative Examples 5-12, although the addition of less than 1% relative to the resin solids met the criteria for haze value, transmittance, and resistance to damp heat of the adhesive film (antistatic adhesive resin) with antistatic properties, the surface resistivity was high. Therefore, although the amount of antistatic agent added was increased to reduce the surface resistivity, the performance of haze value and transmittance decreased, and the adhesion changed significantly. Additionally, in Comparative Examples 13-20, the anionic compound in Examples 1-8 was changed to dodecylbenzenesulfonic acid, but all the criteria required for the adhesive film (antistatic adhesive resin) with antistatic properties formed from the adhesive composition with antistatic properties as the objective of this invention were not met.

[0186] In particular, when comparing Examples 1-8, which are also antistatic agents belonging to tetraalkylammonium dioxolane-borate, with Comparative Examples 1-12, in Comparative Examples 1-4, where the total number of carbons in the tetraalkylammonium is as low as 8, the resin compatibility is poor due to low hydrophobicity. It is considered that when forming an adhesive film (antistatic adhesive resin) with antistatic properties, the haze value and transmittance are reduced, and the adhesion and damp heat resistance properties change significantly. In Comparative Examples 5-12, where the total number of carbons is as high as 19 and 25, the surface resistivity is considered to be higher when forming an adhesive film (antistatic adhesive resin) with antistatic properties due to the increased molecular weight and the reduced conductivity of the antistatic agent. Therefore, it is considered that by setting the total number of carbons of the alkyl groups in the tetraalkylammonium cation containing the embodiments of the present invention to 12-16, all the benchmarks for surface resistivity, resin compatibility, adhesion, and damp heat resistance properties can be effectively met.

[0187] Industrial availability

[0188] This invention can be used for surface protective films, etc., to protect the surface of optical components.

Claims

1. An antistatic agent comprising a quaternary ammonium salt of formula (1), In formula (1), R1 to R4 can be chosen to be the same or different, and are alkyl groups with 1 to 13 carbon atoms, and the total number of carbon atoms of the alkyl groups of R1 to R4 is 12 to 16.

2. The antistatic agent according to claim 1, wherein, The quaternary ammonium salt represented by formula (1) is tetrabutylammonium = dioxaborate or tetrapropylammonium = dioxaborate.

3. An antistatic resin, characterized in that, It contains the antistatic agent and resin as described in claims 1 to 2.

4. An adhesive composition, characterized in that, It contains the antistatic agent as described in claims 1 to 2 and an acrylic adhesive.

5. The adhesive composition according to claim 4, characterized in that, Relative to 100 parts by weight of the resin component of the acrylic adhesive, it contains 0.1 to 10 parts by weight of antistatic agent.

6. An antistatic adhesive resin, characterized in that, The adhesive composition of claim 4 contains a surface resistivity of less than 1.0 × 10⁻⁶. 10 Ω.

Citation Information

Patent Citations

  • Pressure-sensitive adhesive composition, pressure-sensitive adhesive sheets, and surface protection film

    JP2005290357A

  • Adhesive composition, adhesive article, adhesive composition for optical use, and adhesion method

    JP2013064146A

  • Antistatic agent and antistatic resin composition

    JP2019108414A

  • Adhesive sheet for semiconductor device protection

    JP2022109631A

  • Ionic liquid and Anti-static agent

    JP2023034983A